2022
DOI: 10.1242/dev.200899
|View full text |Cite
|
Sign up to set email alerts
|

A mutation in THREONINE SYNTHASE 1 uncouples proliferation and transition domains of the root apical meristem: experimental evidence and in silico proposed mechanism

Abstract: A continuum from stem to transit-amplifying and to a differentiated cell state is a common theme in multicellular organisms. In the plant root apical meristem (RAM), transit-amplifying cells are organized in two domains, the proliferation domain (PD) from which the cells are displaced to the transition domain (TD), suggesting that both domains are necessarily coupled. Here we show that in a mutant, affected in threonine (Thr) synthesis (methionine overexpressor2-2), the RAM lacks the PD. Through a combination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…In such a case we believe that one way to address the limitations of this model, particularly those related to those mutants partially recovered by our approach, is to extend this GRN through a spatial lattice-based formalism, which shall allows us to extend this model to a continuum approach and where we can simulate the processes of cell diffusion and communication in a more fine-grained manner. It has been demonstrated the utility of this approach in previous models to explain the system-level dynamics of root apical meristem [45, 46].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In such a case we believe that one way to address the limitations of this model, particularly those related to those mutants partially recovered by our approach, is to extend this GRN through a spatial lattice-based formalism, which shall allows us to extend this model to a continuum approach and where we can simulate the processes of cell diffusion and communication in a more fine-grained manner. It has been demonstrated the utility of this approach in previous models to explain the system-level dynamics of root apical meristem [45, 46].…”
Section: Discussionmentioning
confidence: 99%
“…demonstrated the utility of this approach in previous models to explain the system-level dynamics of root apical meristem[45,46].…”
mentioning
confidence: 95%
“…In such a case we believe that one way to address the limitations of this model, particularly those related to those mutants partially recovered by our approach, is to extend this GRN through a spatial lattice-based formalism, which allows us to extend this model to a continuum approach and where we can simulate the processes of cell diffusion and communication in a more fine-grained manner. It has been demonstrated the utility of this approach in previous 38/49 models to explain the system-level dynamics of root apical meristem [44,45].…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…It is this kind of complex, often bi-directional regulatory interactions and intracellular, intercellular, and tissue-level processes that necessitate the use of multi-scale models to unravel the mechanisms underlying root tip regeneration. Previous research in intact roots has demonstrated the power of combining computational modeling with experimental research, revealing how the combined activity of a suite of molecular regulators drives root SCN patterning, auxin gradient formation, developmental zonation, postembryonic development, and lateral root prepatterning (e.g., Garc ıa-G omez et al, 2020Garc ıa-G omez et al, , 2022Grieneisen et al, 2007;M€ ah€ onen et al, 2014;Mironova et al, 2012;Salvi et al, 2020;van den Berg et al, 2021). In the context of root regeneration, this approach can be harnessed to integrate the different pieces of the root regeneration puzzle, summarized here, into multi-scale computational models.…”
Section: Toward a Multi-scale Understanding Of Root Regenerationmentioning
confidence: 99%
“…To introduce the major players, their spatial domain of activity, and the targeted end state of regeneration, here we first discuss the major aspects of root developmental patterning in intact roots. The indeterminate growth of the root is driven by the activity of stem cells located at the root apex, housed in a molecular microenvironment where the genetic, hormonal, and metabolic conditions maintain them in an undifferentiated state (Cruz‐Ramírez et al., 2012; Galinha et al., 2007; García‐Gómez et al., 2020, 2021, 2022; Long et al., 2017; Mähönen et al., 2014; Sabatini et al., 1999; Salvi et al., 2020; Strotmann & Stahl, 2021; Tsukagoshi et al., 2010; Weits et al., 2021). The root stem cell niche (SCN) consists of the QC cells, surrounded by different sets of initials cells that produce in a stereotypical radial organization vascular, pericycle, cortex/endodermis, epidermis/lateral root cap, or columella cells (Figure 1a).…”
Section: Setting the Stage: Patterning In Intact Rootsmentioning
confidence: 99%